The Post-Discharge Growth of Very Low Birth Weight Preterm Infants - Tuba Ozdemir; Abdullah Baris Akcan; Munevver Kaynak Turkmen (Medical Network, 2020)
OBJECTIVE: In the present study, we investigate the growth characteristics of very low birth weight premature infants of up to two years corrected age, considering the factors affecting growth and catch-up growth time. STUDY DESIGN: The demographic data, clinical features, and comorbidities of 77 preterm infants with birth weights of less than or equal to 1.500 g were examined, the infants' growth statuses in the 40th gestational week (gw) and at 6, 12, 18 and 24 months the corrected age, including their weight, height and head circumference, were evaluated. RESULTS: The findings revealed that very low birth weight infants should be closely monitored either during their stay in the Neonatal Intensive Care Unit, or for up to 6 months corrected age, paying particular attention to growth data, and the appropriate supportive treatment should be administered. The applied support process is influential on the future somatic growth of preterm infants. It was noted in the study that bronchopulmonary dysplasia, proven sepsis, respiratory distress syndrome, steroid treatment for more than three days, patent ductus arteriosus, and ibuprofen treatment seemed to affect somatic growth negatively. CONCLUSION: Small for gestational age newborns were found to catch up with appropriate for gestational age newborns at 2 years corrected age in terms of growth, although the percentage of catch-up growth during follow-up at the 40thgw, and at the 6th, 12th and 18th months was lower than that of appropriate for gestational age newborns.